Preparing an independent generation: Sharpening language, instilling integrity and building self-reliance - Febriyanti, Doris; Amaliatulwalidain, Amaliatulwalidain; Anggraini, Nike (Universitas Muhammadiyah Magelang, 2025)
Empowering adolescent girls in orphanages is crucial for enhancing their self-reliance and readiness for the future. This community service program aimed to equip adolescent girls at Panti Aisyiyah Humairah with English language skills (focusing on daily conversation), instill integrity (anti-corruption values), and build self-reliance (cooking techniques, food safety, culinary business opportunities). The training methodology involved theoretical sessions, practical application, and skill evaluation. Evaluation results showed a significant improvement in participants' understanding and competency, with average scores increasing from 3.3–4.2 to 4.3–4.6, notably in key knowledge/skill aspects measured. This program proved effective in comprehensively enhancing the capacity of adolescent girls, expected to broaden their employment and entrepreneurial opportunities, while also fostering their motivation and independence.